Implementation of the Smart Indonesia Program (PIP) at Elementary School (SD) Level in Citangkil District - Diang Artie Kanisyah Putri (Epistemik Press, 2024)
Poverty is one of the factors that cause low school enrollment rates and high dropout rates. So to overcome these problems, the government issued a policy program, namely the Smart Indonesia Program (PIP). The Indonesia Smart Program (PIP) is assistance in the form of cash, expansion of access, and learning opportunities from local governments provided to students and students who come from poor families. However, in its implementation, the Smart Indonesia Program (PIP) still has several problems. So the focus of this research is the implementation of the Smart Indonesia Program (PIP), with the aim of knowing the implementation of the Smart Indonesia Program (PIP) at the elementary school level in Citangkil District. The research method used is qualitative research method. The results of this study indicate that the implementation of the Smart Indonesia Program (PIP) at the elementary school level in Citangkil District has gone well, this can be seen from the achievement of all aspects of public policy implementation according to Van Metter and Van Horn (2017: 133), so that the objectives of the Smart Indonesia Program (PIP) can be achieved.